Genome sequencing reveals a new lineage associated with lablab bean and genetic exchange between Xanthomonas axonopodis pv. phaseoli and Xanthomonas fuscans subsp. fuscans - Aritua, Valente; Harrison, James; Sapp, Melanie; Buruchara, Robin; Smith, Julian; Studholme, David J. (Frontiers in Microbiology, 2015)
Common bacterial blight is a devastating seed-borne disease of common beans that also occurs on other legume species including lablab and Lima beans. We sequenced and analysed the genomes of 26 isolates of Xanthomonas axonopodis pv. phaseoli and X. fuscans subsp. fuscans, the causative agents of this disease, collected over four decades and six continents. This revealed considerable genetic variation within both taxa, encompassing both single-nucleotide variants and differences in gene content, that could be exploited for tracking pathogen spread. The bacterial isolate from Lima bean fell within the previously described Genetic Lineage 1, along with the pathovar type isolate (NCPPB 3035). The isolates from lablab represent a new, previously unknown genetic lineage closely related to strains of X. axonopodis pv. glycines. Finally, we identified more than 100 genes that appear to have been recently acquired by Xanthomonas axonopodis pv. phaseoli from X. fuscans subsp. fuscans.